Sex and Gender Differences in the Brain Cholinergic System and in the Response to Therapy of Alzheimer Disease with Cholinesterase Inhibitors - Giacobini, Ezio; Pepeu, Giancarlo (Current Alzheimer Research, 2018)
This review has two aims. First, to examine whether or not sex and gender may influence the brain cholinergic system in animals and in humans. Second, to examine the available evidence of sexually dimorphic response to the therapeutic and toxic effects of cholinesterase inhibitors. Animal research reveals no marked difference in the general morphology of the brain cholinergic system but subtle functional gender differences have been reported. In humans, gender differences in nucleus basalis of Meynert (NBM) exist. In animals, some cholinergic neurons express estrogen alpha receptors in females and androgens in males. It is known that sex hormones exert trophic effects on the cholinergic system. Females show higher frontal cortex cholinergic activity whereas males have higher activity in the hippocampus. Gender differences in the pharmacological effects result in higher sensitivity to the toxic effects of organophosphate cholinesterase inhibitors in males. A stronger and more selective benefit of ChEI treatment in AD has been reported in men by several authors. Sex and estrogen receptor phenotype may both influence the response to donepezil and rivastigmine. Hence, aged male and female individuals might respond differently to ChEI due to either sex-specific differences in structures and function of the cholinergic system, pharmacokinetics, memory function or in the way aging or AD affects these processes.
Keywords: nucleus basalis magnocellularis